Evaluating the Quality of an ELT Program in Higher Education - Özlem Grab Melissa (Journal of Education, Society & Multiculturalism, 2025)
This is a mixed-methods case study that explores a higher education institution's ELT bachelor's degree program curriculum in terms of compliance with the accreditation standards and to what extent it leads to improved student learning outcomes. For both quantitative and qualitative research methods, the sample size targeted 120 students, 10 faculty members, and 5 external stakeholders. Data on perceived effectiveness of the curriculum and levels of satisfaction were measured by a structured questionnaire, while semi-structured interviews aimed at eliciting qualitative information about strengths and identified areas for curriculum improvement. Indeed, 85% of the students felt sufficiently qualified to teach the subject of English, while 90% of the educators believed the program conformed appropriately to the standards for accreditation. However, there was consensus from both groups on areas of improvement, which included better integration of technology and more practical exposure to teaching. Interview data from thematic analysis indicated the commitment of faculty and continuous curriculum review. These findings inform recommendations for integration of technology in the curriculum, as well as strengthening collaboration with local schools and a scheduled process for reviewing curriculum.